Role of information systems in supply chain management optimization: Rôle des systèmes d’information dans l’optimisation de management de la supply chain - CHAIMAE, RKAYNA (African Scientific Journal, 2021)
Abstract The information system plays an important role in optimizing the supply chain management (planning and performance, platform and transport), in order to ensure good coordination between them, as well as allowing optimization of the supply chain (production, storage, and transport) (BOUROUBA 2013). This paper presents the role of information systems in optimization of the supply chain management and it application in CEVITAL Company. Key word: Supply chain management , information system.